1999
DOI: 10.1097/00000539-199908000-00043
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Ramosetron and Granisetron for Preventing Postoperative Nausea and Vomiting After Gynecologic Surgery

Abstract: We compared the efficacy of granisetron and ramosetron for preventing postoperative nausea and vomiting in major gynecologic surgery. Prophylactic therapy with ramosetron was more effective than granisetron for preventing postoperative nausea and vomiting 24-48 h after anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 12 publications
2
23
0
1
Order By: Relevance
“…Ramosetron (Table 5) Two studies have compared the efficacy of ramosetron 0.3 mg and granisetron 2.5 mg administered i.v. at the end of surgery for the prevention of PONV in female patients undergoing gynecologic surgery, or laparoscopic cholecystectomy [66,67]. In these investigations, the antiemetic efficacy of ramosetron was similar to that of granisetron for the prevention of PONV during 0-24 h after anesthesia, and ramosetron was more effective than granisetron for increasing the number of patients who were emesis-free during 24-48 h after anesthesia.…”
Section: Introductionmentioning
confidence: 83%
“…Ramosetron (Table 5) Two studies have compared the efficacy of ramosetron 0.3 mg and granisetron 2.5 mg administered i.v. at the end of surgery for the prevention of PONV in female patients undergoing gynecologic surgery, or laparoscopic cholecystectomy [66,67]. In these investigations, the antiemetic efficacy of ramosetron was similar to that of granisetron for the prevention of PONV during 0-24 h after anesthesia, and ramosetron was more effective than granisetron for increasing the number of patients who were emesis-free during 24-48 h after anesthesia.…”
Section: Introductionmentioning
confidence: 83%
“…VAS was measured every hour up to 6 h postoperatively, and then at 6 h intervals for 24 h. Whenever the VAS score was C4 or the patient requested pain medication, analgesia was provided by meperidine 0.5 mg/kg iv. Satisfaction score was measured on a linear numerical scale; ranging from 0 = complete dissatisfaction to 10 = complete satisfaction [15]. Any postoperative side effects, for example nausea, vomiting, itching, bradycardia, hypotension, excessive sedation, inadequate analgesia, retention of urine, or respiratory depression defined as respiratory rate \10/min or SpO 2 \90%, were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…In this investigation, the antiemetic efficacy of ramosetron was similar to that of granisetron for preventing PONV during 0-24 h after anesthesia, and ramosetron was more effective than granisetron in decreasing the incidence of PONV during 24-48 h after anesthesia [22]. Similarly, ramosetron 0.3 mg was more effective than granisetron 3 mg for the prophylaxis against PONV during 24-48 h after anesthesia in 80 women undergoing laparoscopic cholecystectomy [23], 100 patients (31 men and 69 women) undergoing middle ear surgery [24], 90 women undergoing breast surgery [25], and 80 patients (15 men and 65 women) undergoing thydroidectomy [26].…”
Section: Prevention Of Ponv With Ramosetron In Adults (Table 1)mentioning
confidence: 67%
“…Similarly, ramosetron 0.3 mg was more effective than granisetron 3 mg for the prophylaxis against PONV during 24-48 h after anesthesia in 80 women undergoing laparoscopic cholecystectomy [23], 100 patients (31 men and 69 women) undergoing middle ear surgery [24], 90 women undergoing breast surgery [25], and 80 patients (15 men and 65 women) undergoing thydroidectomy [26]. The efficacy of both SRAs was comparable for preventing PONV during 0-24 h after anesthesia in these surgical patients [22][23][24][25][26]. By contrast, Lee et al demonstrated that antiemetic efficacy of ramosetron 4 mcg kg -1 was not superior to granisetron 20 mcg kg -1 for preventing PONV during 0-24 h after anesthesia in 113 patients (19 men and 94 women) undergoing thyroidectomy.…”
Section: Prevention Of Ponv With Ramosetron In Adults (Table 1)mentioning
confidence: 97%